Analytical-numerical solution of a parabolic diffusion equation under uncertainty conditions using DTM with Monte Carlo simulations (2015)
A numerical method to solve a general random linear parabolic equation where the diffusion coefficient, source term, boundary and initial conditions include uncertainty, is developed -- Diffusion equations arise in many fields of science and engineering, and, in many cases, there are uncertainties due to data that cannot be known, or due to errors in measurements and intrinsic variability -- In order to model these uncertainties the corresponding parameters, diffusion coefficient, source term, boundary and initial conditions, are assumed to be random variables with certain probability distributions functions -- The proposed method includes finite difference schemes on the space variable and the differential transformation method for the time -- In addition, Monte Carlo method is used to deal with the random variables -- The accuracy of the hybrid method is investigated numerically using the closed form solution of the deterministic associated